Finance and Development, December 1971. (Finance and Development; Finance and Development ;, 1971)
This paper discusses the employment of women in developing countries in the light of recent changes in emphasis on the strategy and objectives of economic development. The paper highlights that in the vast majority of countries-both developed and developing-the role of women is still limited and their responsibilities restricted. This paper examines automated manufacturing techniques in developing economies. The operations and transactions of the special drawing account are discussed. The paper also analyzes Latin America's prospects for overcoming historical attitudes and other constraints to achieve wider economic integration.